Viral epidemiology of the adult Apis Mellifera infested by the Varroa destructor mite. Issue 5 (May 2016) - Bernardi, Sara; Venturino, Ezio
Abstract: The ectoparasitic mite Varroa destructor has become one of the major worldwide threats for apiculture. Varroa destructor attacks the honey bee Apis mellifera weakening its host by sucking hemolymph. However, the damage to bee colonies is not strictly related to the parasitic action of the mite but it derives, above all, from its action as vector increasing the transmission of many viral diseases such as acute paralysis (ABPV) and deformed wing viruses (DWV), that are considered among the main causes of CCD (Colony Collapse Disorder). In this work we discuss an S I − S I model that describes how the presence of the mite affects the epidemiology of these viruses on adult bees. The acronym S I − S I means that the disease affects both populations. In fact it accounts for the bee and mite populations, that are each divided among the S (susceptible) and I (infected) states. We characterize the system behavior, establishing that ultimately either only healthy bees survive, or the disease becomes endemic and mites are wiped out. Another dangerous alternative is the Varroa invasion scenario with the extinction of healthy bees. The final possible configuration is the coexistence equilibrium in which honey bees share their infected hive with mites. The analysis is in line with some observed facts in natural honey bee colonies. Namely, these diseases are endemic. Further, if the mite population is present, necessarily the viral infection occurs. The findings of this study indicate that a low horizontal transmission rate of the virus among honey bees in beehives will help in protecting bee colonies from Varroa infestation and viral epidemics.